The discursive portrayals of Indonesian Muslims and Islam in the American press: A corpus-assisted discourse analysis - Fajri, Muchamad Sholakhuddin Al (Indonesian Journal of Applied Linguistics, 2019)
Numerous studies across disciplines on how western media portray Muslims have been conducted in different geopolitical and cultural contexts. However, we still lack research into media constructions of Muslims from a particular country, including Indonesia, which is the most populous Muslim nation. This study aims to analyse the linguistic representation of Indonesian Muslims and Islam in two corpora of American newspapers published in two different five-year periods (2002-2006 and 2012-2016) by using corpus-assisted discourse analysis framework. Keyword, collocation and concordance analyses were employed to reveal dominant discourses of Indonesian Muslims. It was also enriched by critical discourse studies’ commitment to analysing social and political contexts. Some of the findings corroborate and reinforce the results of previous studies on media depictions of Muslims in general, in that the dominant discourses around Islam and Muslims are related to terrorism, fundamentalism, conflict and violence. However, this study also brings forward additional information, including a shift in the discourse. Dominant discourses around Indonesian Muslims in the American newspapers have witnessed a slight change over the 15 year-period from terrorism and extremism to radicalism only. What might be highlighted is that there are extremely few positive media portrayals of either Muslims in general or Indonesian Muslims.